(NmASS(B-(NSPEKTRALXNYJ ANALIZ SMESEJ S PRIMENENIEM IONNO(B-(NMOLEKULQRNYH REAKCIJ (B/s - (NpOLQKOWA(B, (NaDA aLEKSANDROWNAs; (NrEWELXSKIJ(B, (Ni(B.(Na(B.s; (NtOKAREW(B, (Nm(B.(Ni(B.s; (NpOLQKOWA(B, (NaDA aLEKSANDROWNAs ((NmOSKWA (B:s (NhIMIQ(B,s, 1989)
(NbIBLIOGR(B.: (NS(B. 231-240 (347 (NNAZW(B.)s
(NaWT(B. (NUKAZANY NA OBOROTE TIT(B. (NL(B.s
Keywords: (NmASS(B-(NSPEKTROMETRIQs